2014
DOI: 10.2147/ijn.s57735
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of graphene oxide reduced by Ganoderma spp. in human breast cancer cells (MDA-MB-231)

Abstract: Background Recently, graphene and graphene-related materials have attracted much attention due their unique properties, such as their physical, chemical, and biocompatibility properties. This study aimed to determine the cytotoxic effects of graphene oxide (GO) that is reduced biologically using Ganoderma spp. mushroom extracts in MDA-MB-231 human breast cancer cells. Methods Herein, we describe a facile and green method for the reduction of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 75 publications
6
91
0
Order By: Relevance
“…23,32 Briefly, rGO was obtained from the reaction of C-phycocyanin with GO. In a typical reduction experiment, 10 mL C-phycocyanin (10 mg) was added to 90 mL 1 mg/mL aqueous GO; the mixture was stirred at 30°C for 12 hours.…”
Section: Synthesis Of Agnps and Go And Reduction Of Gomentioning
confidence: 99%
See 2 more Smart Citations
“…23,32 Briefly, rGO was obtained from the reaction of C-phycocyanin with GO. In a typical reduction experiment, 10 mL C-phycocyanin (10 mg) was added to 90 mL 1 mg/mL aqueous GO; the mixture was stirred at 30°C for 12 hours.…”
Section: Synthesis Of Agnps and Go And Reduction Of Gomentioning
confidence: 99%
“…53 Also, recently we observed that both GO and AgNPs were capable of inducing ROS in several cancer cell lines. 21,22,32 Therefore, we were interested to investigate whether Cis, rGO-AgNPs, or a combination of Cis and rGO-AgNPs induced a dramatic effect on ROS-induced cell toxicity. To study the oxidative impact of Cis and rGOAgNPs on cellular oxidation-reduction (redox) state, we measured cellular ROS levels after exposing HeLa cells to Cis, rGO-AgNPs, or a combination of both for 24 hours.…”
Section: Rgo-agnps Enhance Cytotoxic Effect Of Cismentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Owing to its excellent characteristics, graphene can be potentially used in electronic devices such as flexible thin-film transistors, touch panels, and solar cells. [5][6][7]10 Furthermore, graphene has been used in various biomedical applications such as bio-sensing, 11 antibacterial composites, [12][13][14] drug delivery, 15 and tissue scaffolds.…”
mentioning
confidence: 99%
“…6,7,26 The most commonly used chemical-reducing agents are hydrous hydrazine, hydrazine monohydrate, sodium borohydride, and hydrogen sulfide, which are highly toxic and harmful to living organisms and the environment. 6,9,[26][27][28] To overcome the aggregation and solubility problems, several polymers or surfactants have been used such as poly(sodium-4-styrenesulfonate), 29 alkaline conditions, 30 poly(N-vinyl-2-pyrrolidone), 31 and poly(allylamine). 32 Recently, biological molecules have been used to reduce GO; thus, Salas et al 33 have reported "green" reduction of GO via bacterial respiration.…”
mentioning
confidence: 99%